Hypersomnolence is associated with non-remission of major depressive disorder - Cheung, Maxine Ming Sum; Lam, Siu Ping; Chau, Steven Wai Ho; Chan, Ngan Yin; Li, Tim MH; Wing, Yun Kwok; Chan, Joey W.Y. (Sleep medicine, 2024)
This study aimed to investigate the prevalence, clinical correlates and the relationship between hypersomnolence and clinical outcomes in a cohort of MDD patients. This is a cross-sectional study of a MDD cohort in an university-affiliated adult psychiatric outpatient clinic. The diagnosis of MDD and severity of depression were ascertained by the clinician with structured clinical interviews. Each participant completed the Epworth Sleepiness Scale (ESS), 1-week sleep diary, and a battery of questionnaires that assessed usual sleep pattern, insomnia, anxiety, depression, fatigue and circadian preference. Hypersomnolence was defined as ESS score ≥14 among those reported ≥7 h of nighttime sleep. Univariate analysis and multiple logistic regression were used to analyze the relationships between the variables. Among 252 recruited subjects, 11 % met the criteria of hypersomnolence as defined by a ESS score ≥14 despite ≥7 h of nighttime sleep. Patients with hypersomnolence had greater depression ratings, higher rates of suicidal ideations over the past week, and more likely to meet a diagnosis of atypical depression (p < 0.05) than those without hypersomnolence. Step-wise logistic regression demonstrated that hypersomnolence was an independent risk factor associated with a 3-fold increase in the risk of depression non-remission (adjusted OR 3.13; 95 % CI 1.10–8.95; p = 0.034). Patients with hypersomnolence despite seemingly adequate sleep represent a subgroup of MDD patients who have a more severe illness profile with higher non-remission rate and suicidality. The findings highlight the importance of addressing both sleep and mood symptoms in the management of MDD. •EDS despite adequate sleep is a common problem in MDD (11 %).•Hypersomnolence is associated with a 3-fold increase in risk of non-remission.•Comprehensive assessment of hypersomnolence is needed to improve the depression outcomes.